To love and be wise : with a new introduction by Robert Barnard - Tey, Josephine, 1896 or 1897-1952 (Inspector Alan Grant, 1998)
When a young strikingly handsome photographer mysteriously disappears, it's up to Inspector Alan Grant to discover whether he accidentally drowned, committed suicide, or met his death at the hands of one of his many female admirers.